Alleviation of poverty through entrepreneurship in savings and credit associations – Stokvels – a case study from South Africa - Anthony Kambi Masha; Siphenathi Fihla (Insights into Regional Development)
Women, especially widows, have always faced different forms of discrimination and financial exclusion. During the COVID-19 pandemic, most economic activities came to a standstill, resulting in a struggle for survival for widows involved in stokvel-preneurship. This study is set against the background that although studies on stokvels exist and, whilst negative impacts of the COVID-19 pandemic have been felt across the country, little is known about how widows involved in stokvel-preneurship in the Eastern Cape province went on with their stokvel activities during the COVID-19 pandemic to alleviate poverty, a gap that this study aims to address. We used a quantitative process by employing a positivist paradigm from a unique axiology, ontology, epistemology, technique, and rhetorical stance. Data were collected using questionnaires and analysed a T-independent test was employed as a data analysis tool to test the significance difference between the mean groups. Descriptive statistics were used to describe the features and summaries of the study's data set. The study found that widows could continue their stokvel businesses during the COVID-19 pandemic. The study concluded that the COVID-19 pandemic was a huge disruptor, but widows involved in this study moved on with their stokvel activities because they needed to survive.